(3GdeYjfs - (3MHjH Gddg Hf bGVjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3jHOC HHGH GdWgGQI Hbhdg (B: (3HGH GdHGH dZI aQLI ai SGJQ jJhUd HgG ef OGNd Edi NGQL Ch GdYcS hTQYkG GSe GdWGFaI ef eSGFd GdYde eTJQcI ai eYfi hGMO Ch eJbGQHg ajg hgh gfG ddWgGQI s
(3BNQgG (B:s
(3jfJgi HHGH GdfabI Hbhdg aEPG cGf GdMGV CeG eYeSQI hGdhdO ehSQ adgG GdfabI ddbQGHI dG ddMVGfI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTjgG HYV GdTQhM hGdEVGaGJ HGdMHQ GdCShO hGdCMeQs
(3hGdUaMGJ GdChdi efgG GXgQJ HMHQ eZGjQ s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3Gdabg GdESdGejs